KELAYAKAN FINANSIAL USAHA PENGOLAHAN KERUPUK AMPLANG DI KECAMATAN BENUA KAYONG KABUPATEN KETAPANG - Siregar, Anggitio Aprian; Yurisinthae, Erlinda; Suyatno, Adi (Jurnal Sains Pertanian Equator, 2024)
Industry is a business or activity that processes raw materials or semi-finished goods into goods that have added value to make a profit. Amplang is a product made from fish mixed with tapioca flour and is very popular with the public. This food is often used as a complement to meals or as a snack. The development of small industries is one of the focuses of the Ministry of Industry because MSMEs make a large contribution to the formation of non-oil and gas processing industry GDP. In the last five years there has been an increase of 2.5 percent from 57.84 percent to 60.34 percent (Performance Report of the Indonesian Ministry of Industry, 2018). Based on the number of businesses/companies according to business field categories and small business scale, the processing industry is in the third largest position, namely 4,373,821 business units spread across Indonesia (Central Statistics Agency, 2015). It is very important to carry out studies regarding feasibility analysis, one of which is as a reference for Amplang business owners in running businesses in the business sector. Analysis is carried out to assess the feasibility of a business from a financial aspect.